Medical practitioner compassion: Development and validation of a compassion competency questionnaire - Michelle Jäckel-Visser; Carl C. Theron; Robert J. Mash (African Journal of Psychological Assessment, 2025)
There is a need for a psychometrically robust questionnaire measuring medical practitioner compassion in healthcare. Without such a measure, competence on this construct cannot be assessed, nor can the effectiveness of interventions designed to enhance compassion be determined. The aim of this study was to develop and validate a self-assessment measure of medical practitioner compassion competence (the Medical Practitioner Compassion Competency Questionnaire [MPCCQ]). The MPCCQ was administered to a sample of 234 medical practitioners in South Africa. They represented three healthcare system levels, namely, the primary level (healthcare centres and clinics), the secondary level (district and regional hospitals) and the tertiary level (central, specialised and sub-specialist hospitals). The quantitative data were analysed with statistical packages, namely, Statistical Package for the Social Sciences (SPSS) version 25 and LISREL 8.8, and structural equation modelling was used to fit the MPCCQ measurement model and structural model. Dimensionality and item analyses returned generally positive results. Fit statistics and criteria used to judge the fit of the models included Chi-square (χ2), goodness of fit index (GFI), adjusted goodness of fit index (AGFI), root mean square error of approximation (RMSEA), root mean square residual (RMR) and the standardised root mean square residual (SRMR). The results provided an excellent model fit for both the measurement and comprehensive LISREL models. The MPCCQ, measurement and structural model parameter estimates supported the position that the design intention underpinning the MPCCQ succeeded.